Theoretical prediction and crashworthiness optimization of thin-walled structures with single-box multi-cell section under three-point bending loading. (July 2019) - Du, Zhanpeng; Duan, Libin; Cheng, Aiguo; Xu, Zhidan; Zhang, Guangya
Highlights: A theoretical prediction model is developed to reveal the collapse mechanism of TWS-SMC. A theoretical formula is given to predict the energy-absorption of the structures under three-point bending loading. The efficiency of design optimization for TWS-SMC is improved significantly using the theoretical-formulas based optimization. The energy-absorption capacity of TWS-SMC is superior to the TWS-S1C under the same mass, and its energy-absorption capacity will improve gradually with the number of web parts increased. Abstract: This paper aims to study the bending collapse behavior and energy absorption mechanism of thin-walled structures with single-box multi-cell section (TWS-SMC). A theoretical prediction model of TWS-SMC is developed under three-point bending loading. The theoretical prediction formulas are also derived by dividing the TWS-SMC into web parts and flange parts. The accuracy and generality of the theoretical prediction formulas are validated by performing three-point bending test and finite element analysis (FEA). To further validate the theoretical prediction formulas and improve the energy-absorption capacity, both theoretical prediction formulas and FEA based surrogate models are employed to perform the crashworthiness optimization of the TWS-SMC. The results show that (i) the Pareto frontiers obtained from the theoretical prediction formulas show an excellent coincidence with those from the FEA based surrogate models, which means that the theoretical prediction formulas can be directly used to crashworthiness optimization design for the sake of computational efficiency; (ii) the energy-absorption capacity of TWS-SMC is superior to thin-walled structures with single-box one-cell section (TWS-S1C) under the same weight, and its energy-absorption capacity will improve gradually with the number of web parts increased.